The Effectiveness of Construct 2-Based Educational Games in Enhancing Arabic Vocabulary Acquisition and Listening Skills Among Junior High School Students - Mohammad Ahsanuddin; Muhammad Ahsan Thoriq; Najma Auliya' Maulidah Ahsan; Farika Riskiyah (Universitas Ahmad Dahlan, 2025)
Secondary-school Arabic teachers frequently report low student involvement, limited vocabulary growth, and weak listening comprehension when instruction relies mainly on lectures. To address these issues, the present study tested whether instructional games created with the Construct 2 engine could improve vocabulary and listening skills among junior-high learners. Adopting a quasi-experimental, non-equivalent control-group pretest-posttest design, the research arranged participants into three sections: an experimental group taught with Construct 2 games, a positive control group receiving enriched traditional lessons, and a negative control group exposed solely to lecture delivery. ANCOVA analysis uncovered a statistically significant group effect, F(2, 26) = 65.14, p = .021, accompanied by a large η² = 0.95. Follow-up post hoc comparisons showed that the experimental group (M = 75.6) outpaced both control sections (M = 68.9 and M = 67.2, p < .001). Overall, results indicate that game-based learning can reliably enhance receptive language abilities and warrants further adoption in Arabic classrooms. These findings speak directly to how teachers and administrators might structure courses and introduce new techniques, especially where money and materials are scarce.